Controller Design for Electric Motor Derived Vehicle - Nitin Kumar Saxena; Sirak Gebrehiwot; Degu Mena (IAES Indonesian Section, 2018)
In this paper, proportional and integral based controller is designed for controlling the output voltage of battery. This battery is used for operating an electric motor derived vehicle. It has been represented that without any control mechanism the output voltage cannot be controlled and it will give a large deviation in output voltage in terms of error signal and that will decline the battery output current as a result battery power output will reduce and therefore the performance of electric motor derive vehicle will go down in terms of power and torque to derive vehicle. So, it is mandatory to maintain the output voltage of the battery and that can be achieved by a proper feedback control system. A PI based controller is designed and implemented for this electric motor derived vehicle in the present paper. Paper demonstrates how the results improve in presence of controller circuit for this electric motor derived vehicle.